Indirect georeferencing of terrestrial laser scanning data using control lines - Dos Santos, Daniel R.; Dal Poz, Aluir P. [UNESP]; Khoshelham, Kourosh (Wiley, 2013)
An indirect method for the georeferencing of 3D point clouds obtained with terrestrial laser scanning (TLS) data using control lines is presented. This technique could be used for rapid data acquisition where resources do not permit the use of expensive navigation sensors or the placement of pre-signalised targets. The most important characteristic is the development of a mathematical model based on the principle that the direction vector of the TLS straight line is coplanar with the plane defined by the origin of the TLS system, one endpoint of a control line and the direction vector of the control line in the ground reference coordinate system. The transformation parameters are estimated by minimising the distance between the control lines and their corresponding TLS straight lines. The proposed method was tested using both simulated and real data, and the advantages of this new approach are compared with conventional surveying methods. © 2013 This article is a U.S. Government work and is in the public domain in the USA.
Keywords: Adjacent planes; Control lines; Indirect georeferencing; Terrestrial laser scanning data; Georeferencing; Navigation sensors; Rapid data acquisition; Reference coordinate system; Terrestrial laser scanning; Transformation parameters; Mathematical models; Seebeck effect; Steel beams and girders; Surveying instruments; coordinate; data acquisition; laser method; numerical model; plane; surveying; three-dimensional modeling; vector